2013
DOI: 10.1080/10288457.2013.826970
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Context-based and Traditional Approaches in Teaching Genetics: Student Views and Achievement

Abstract: The study aimed to determine the comparative effectiveness of context-based and traditional teaching approaches in enhancing student achievement in genetics, problem-solving, science inquiry and decision-making skills, and attitude towards the study of life sciences. A mixed method but essentially quantitative research approach involving a quasi-experimental, non-equivalent pre-test post-test control group design was used for the investigation. A total of 190 students from six grade 11 intact science classes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
3
13
0
2
Order By: Relevance
“…In addition, there is also widespread poor performance and negative attitudes towards the subject matter itself (Barmby, Kind & Jones, 2008;Kazeni & Onwu, 2013). In Swaziland, where the study reported here was undertaken, a recent World Bank Report on the status of secondary education noted that overall, Swazi students perform poorly in mathematics and science subjects in public examinations (Marope, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is also widespread poor performance and negative attitudes towards the subject matter itself (Barmby, Kind & Jones, 2008;Kazeni & Onwu, 2013). In Swaziland, where the study reported here was undertaken, a recent World Bank Report on the status of secondary education noted that overall, Swazi students perform poorly in mathematics and science subjects in public examinations (Marope, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, researchers (Gercek & Ozcan, 2015;King, 2007) found that teachers have different misunderstandings about the concept of context-based science teaching. Teachers feel that bringing a context-based approach into the classroom will boost students' understanding of concepts in science, according to the findings of certain studies (e.g., Bennett et al, 2005;Fensham, 2009;Kazeni & Onwu, 2013;Stanisavljević et al, 2016). Some researchers (e.g., Eshetu & Assefa, 2019;Kazeni & Onwu, 2013) found that teachers believe the CTL approach helps students develop problem-solving skills more effectively than the traditional approach.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hargrove and Nietfeld (2014) found that metacognitive instruction significantly encourages students' creative problem-solving. Kazeni and Onwu (2013) noted that context-based learning is significantly better than traditional teaching approaches. In addition, Podschuweit and Bernholt (2017) reported that context-based learning provides opportunities for students to develop their conceptual understanding.…”
Section: Introductionmentioning
confidence: 99%